THE CHURCH OF ALEXANDER NEVSKY - Khidirov, Mukhiddin (Oriental Journal of History, Politics and Law, 2025)
This article highlights the history, architectural features, and religious and cultural significance of the Church of Alexander Nevsky, one of the most important architectural monuments of the Orthodox faith. The stages of the church's construction and its spiritual and educational role in society are discussed. The article emphasizes how the personality of Alexander Nevsky and the ideals embodied in the Russian Orthodox Church are reflected in the church's architecture. The church is considered an important source for academic research in the fields of religious architecture and historical-cultural heritage.